Determining pen surface water in a cattle feedlot with thermal infrared remote sensing - Leiker, Curtis Joseph (Kansas State University, 2010)
Particulate matter (PM) emissions from open beef cattle feedlots depend heavily on the level of water on the pen surface. Wet pen surfaces are able to keep PM emissions low, while dry surfaces have much higher rates of emission. Current research shows that 20-25% surface water content is a critical threshold for minimizing PM emissions from open cattle feedlots. The amount of water on the pen surface will also dictate the level of gaseous emissions, such as ammonia, nitrous oxide, and hydrogen sulfide. Traditional methods of measuring pen surface water are not sufficient within a dense cattle feedlot and cannot provide a continuous method of measurement unattended. The process of using infrared thermometry and meteorological variables to remotely sense surface water provides an inexpensive, ground level approach. Testing in laboratory, outdoor, and feedlot conditions was conducted to analyze the potential of using the thermal inertia remote sensing approach. This approach involved continuous measurement of weighted soil water content, surface temperature of the soil, air temperature, solar radiation, wind speed, and relative humidity. Controlled laboratory testing performed the best at predicting soil water content from the difference in soil surface and air temperature, with the coefficient of determination (R2) at 0.91 for a Smolan silt loam and 0.83 for dry feedlot soil. Outdoor testing achieved mixed results with R2 values only as high as 0.38 for 10-cm soil layer and 0.67 for 5-cm soil layer. Testing in a cattle feedlot with dry, loose manure layer proved to be imprecise, but was able to differentiate surface water levels varying from 4.1% to 9.1% wet basis.
Keywords: Remote Sensing; Feedlot; Thermal infrared; Soil water; Engineering, Agricultural (0539); Engineering, Environmental (0775)